Possess me at midnight - Black, Shayla (Pocket Books paranormal romance, 2009)
To save her brother's life, witch Sabelle Rion must align herself with his greatest enemy, Ice Rykard, who is the only person who can help her protect the Doomsday Diary and save the fate of magickind from evil Mathias and his ruthless Anarki army.